PENGARUH GOOD GOVERNANCE, PENGENDALIAN INTERN DAN GAYA KEPEMIMPINAN TERHADAP KINERJA INSTANSI PEMERINTAH (Studi pada SKPD Kabupaten Siak) - Tanjung, Amries Rusli; ', Istiqomatunnisa; ', Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to test the influence of good governance, internal control and leadership style on performance of local government city of Siak. This research was curried out on the units of works devices of Siak. The population in this research is the employees who work in a work unit of the devices area. The technique used is the sample of purposive sampling. The respondents in this study is echelon officer III and IV. The sample used in this study as much as 75 respondents. Statistical methods are used to test the hypothesis of the research is the analysis of multiple linear regression using the software spss version 21.0.The result of this study indicate that the variable are good governance variables affect the performance of local government with a regression coefficient of 0,239 and 0,024 significant value (alpha<0,05) of tcount>ttable that is 2,300>1,994. Internnal controlvariables affect the performance of the local government with a regression coefficient of 0,173 and 0,007 significant value (alpha<0,05) this shown by the result of tcount>ttable that is 2,788>1,994. And leadership style affect the performance of the local government, with a regression coefficient of 0,480 and 0,012 significant value (alpha<0,05) this shown by the result of tcount>ttable that is 2,578>1,994. Based on the calculation of the coefficient of determination (R2) obtained a value of 0,364. This shows that the influence of the independent variables in the dependent 36,4% and the remaining 63,4% influenced by othe variables.Keywords: Good governance, internal control, leadership style, local government permormance